Effectiveness of Edutrip and Storyselling in Increasing the Value of Environmentally Friendly Creative Economic Products in Super Priority Tourism Destinations - PURWANTO, Purwanto; MISTRIANI, Nina (Journal of Tourism Economics and Policy, 2026)
Indonesia's tourism industry has undergone significant transformation in developing super priority tourism destinations that emphasize sustainability and local creative economy empowerment. This study aims to analyze the effectiveness of integrating edutrip and storyselling in enhancing the value of environmentally friendly creative economy products at Borobudur super priority tourism destination. Using a qualitative approach with instrumental case study design, this research was conducted at Kriya Kayu Rik-Rok through in-depth interviews, participatory observation, focus group discussions, and documentation with 12 tourists and 8 stakeholders. The findings reveal five main themes of tourist perceptions: authenticity and local wisdom, integrated environmental awareness, transformative experiences, emotional value and personal meaning, and willingness to pay premium for sustainable products. The study develops the Sustainable Creative Value Enhancement Model (MPNKB) which demonstrates value transformation through four sequential stages: immersion, exploration, transformation, and integration. The integration of edutrip and storyselling proves effective in creating a "deep value ecosystem" that facilitates cognitive, affective, and behavioral transformation among tourists. This research concludes that the combined approach successfully transforms tourist perspectives toward sustainable consumption and creates emotional attachment to environmentally friendly creative product.